2014
DOI: 10.1002/jts.21940
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Drug Use in a Cohort of Workers 4 Years After an Industrial Disaster in France

Abstract: Two years after the 2001 Toulouse industrial disaster, a longitudinal study was set up to evaluate the impact of the disaster. The current substudy examines the medium-term impact (5 years) the incident had on the mental health of 3,004 participants. As part of the monitoring, data relating to the psychotropic drug use of 2,494 participants were collected from administrative databases 4 years after the disaster. Use of psychotropics was higher among women for anxiolytics (10.4% for men and 15.0% for women), hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 24 publications
1
10
0
13
Order By: Relevance
“…These sex differences remained after controlling for trauma types that were more common in women. 27 A 5-year tracking study on citizens of disaster-stricken areas 28 revealed that women had a higher rate of use of psychoactive drugs (ie, antianxiety drugs, antidepressants, sleeping pills) compared with men. However, female students tended to have higher levels of psychosocial stress and anxiety compared with male students.…”
Section: Discussionmentioning
confidence: 99%
“…These sex differences remained after controlling for trauma types that were more common in women. 27 A 5-year tracking study on citizens of disaster-stricken areas 28 revealed that women had a higher rate of use of psychoactive drugs (ie, antianxiety drugs, antidepressants, sleeping pills) compared with men. However, female students tended to have higher levels of psychosocial stress and anxiety compared with male students.…”
Section: Discussionmentioning
confidence: 99%
“…Na Inglaterra 6 , observou-se elevação no número de prescrições de antidepressivos após a ocorrência de inundações fluviais e marítimas, tendo sido esse aumento mais marcante nas áreas mais próximas do evento. Em uma coorte de trabalhadores franceses, o uso de antidepressivos esteve associado a menor distância da explosão de fábrica de produtos químicos 12 . Aumento da prescrição de antidepressivos foi também observado em populações atingidas por ciclone 8 , terremoto 9 e desastre marítimo 7 .…”
Section: Discussionunclassified
“…Em relação aos ansiolíticos, estudo longitudinal desenvolvido na Holanda mostrou maior incidência de uso desses medicamentos após a explosão de depósito de fogos de artifício 10 . Entre trabalhadores franceses do sexo masculino, a proximidade de fábrica de produtos químicos que explodiu esteve associada ao uso de hipnóticos/sedativos, ao passo que a perda de ente querido no desastre foi associada ao uso de ansiolíticos 12 . Já na Nova Zelândia houve aumento na dispensação de ansiolíticos e de hipnóticos/ sedativos em região atingida por terremoto, em comparação à dispensação desses fármacos no restante do país 11 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The most abundant literature related to drug consumption in the working environment refers to psychotropic drug use, 9,29‐33 and has been considered in view of the economic crisis or after stressors such as an industrial disaster 34‐38 …”
Section: Discussionmentioning
confidence: 99%